Responsabilidad del Estado en el derecho a la reparación integral a las víctimas de sicariato producidas por un error en la ejecución del delito. - Japón Salazar., Nadya Alexandra (2023)
The following research work takes into account the State's responsibility for integral reparation for the victims of hired assassinations caused by error in execution. This topic is of significant interest because it allows us to analyze the latent reality that manifests itself in our country daily. In Ecuador, a hired assassination with a firearm is a crime of great commotion. This is a situation that for a long time has generated violations of people's fundamental rights, primarily their right to live and protect themselves, guaranteed by the State. A new case of this kind occurs every day, according to news reports. Most violent deaths occur in sicariato style and although operations and interventions are in some areas, crimes do not stop. Killers are not afraid to shoot in the midst of civilians or to affect innocent people who are or pass by their targets, leaving collateral victims at the time of executing this crime, which suffer damages, material, psychological, health, etc., many criminal acts remain impune and the victims are not fully compensated. Thus, for the research execution, use was made of the scientific, inductive, deductive, analytical, synthetic and statistical method. This was to carry out a study to know basic concepts applied to crime, and to determine a viable solution to the problem. Therefore, the results obtained enabled us to determine actions that contribute to the effective development of rights. Through a legal proposal, actions were generated for the transformation and active exercise of constitutional rights.